Dog Man : a tale of two kitties - Pilkey, Dav, 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2017)
Dog Man, the newest hero from the creator of Captain Underpants, hasn't always been a paws-itive addition to the police force. While he can muzzle miscreants, he tends to leave a slick of slobber in his wake! This time, Petey the cat's dragged in a tiny bit of trouble--a double in the form of a super-cute kitten. Dog Man will have to work twice as hard to bust these furballs and remain top dog!
At head of title: Tree-House Comix proudly presents.
Keywords: Dog Man (Fictitious character) -- Juvenile fiction; Dogs -- Comic books, strips, etc; Dogs -- Juvenile fiction; Cats -- Comic books, strips, etc; Cats -- Juvenile fiction; Police -- Comic books, strips, etc; Police -- Juvenile fiction; Dogs -- Fiction; Cats -- Fiction; Police -- Fiction; Humorous stories; Graphic novels; Police -- Comic books, strips, etc; Dogs -- Comic books, strips, etc; Cats -- Comic books, strips, etc; JUVENILE FICTION -- Action & Adventure; JUVENILE FICTION -- Comics & Graphic Novels; JUVENILE FICTION -- Humorous Stories; Comic books, strips, etc; Graphic novels; Humorous comics; Graphic novels; Humorous comics